Multinationals and Plant Survivals in Swedish Manufacturing - Roger Bandick (Örebro University School of Business, 2007)
Are multinational enterprises MNEs more likely than none-MNEs, owing to their footlose charater, to close down their plants? The results from using a panel o all Swedish manufacturing plants over the period 1993 and 2002 suggest that MNE plants, and in particular Swedish MNE plants, have higher probability to exit the market than non-MNE plants. The outcome is robust controlling for other variables affecting the survival rates. Among non-MNE plants the probabilities of exit is higher in non-exporting firms than in exporting firms. Moreover, the increased forefin presence in swedish manufacturing seems, due to intesified competition, to have led to higher exit rates of plants in non-exporting non-MNEs. Plants of globally engaged indigenous firms, such as plants of Swedish MNEs and exporting non-MNEs, appear. on the other hand, to have been unaffected of the increased foregin presence.
Keywords: C41; F23; J31; 330; Survival analysis; multinational enterprises; foregin ownership